Laporan Kasus Berbasis Bukti: Depresi pada Epilepsi - Putri, Frilya Rachma; Runtuk, Kresna Septiandy; Ghaydaqila, Calista Felicia; Phernando, Nicholas Kevin (Majalah Kedokteran Indonesia, 2025)
Introduction: Depression affects approximately 22.9% of people with epilepsy (PWE), substantially higher than the general population. This comorbidity is mediated by complex neurobiological mechanisms including neuroinflammation, GABA-glutamate imbalance, and hypothalamic-pituitary-adrenal (HPA) axis dysregulation, and is further exacerbated by psychosocial stigma.Case Presentation: We report the case of a 19-year-old woman with epilepsy diagnosed at age 6 who had been treated with phenytoin for 12 years. She developed depressive symptoms following prolonged bullying and social stigma, presenting with persistent sadness, anhedonia, self-harm behaviors, and subsequent psychotic features. Initial management included sertraline and aripiprazole. A drug-drug interactions between sertraline and phenytoin resulted in ataxia and gait imbalance, necessitating a switch in antiepileptic therapy to levetiracetam, carbamazepine, and clobazam.Methods: A systematic literature review using PubMed, Cochrane, and Google Scholar databases, focusing on studies published between 2018 amd 2023 evaluating antidepressant treatment in PWE.Result: Selective serotonin reuptake inhibitors (SSRIs) are recommended as first-line treatment for depression in epilepsy (recommendation level B). Venlafaxine reduced Hamilton Depression Rating Scale (HAMD) scores by 7.59 points compared with no treatment (RR 3.25; 95%CI 1.19–8.90; NNT = 4). Paroxetine versus doxepin demonstrated an RR of 1.16 (95%CI 0.88–1.52; NNT = 9), while amitriptyline versus nomifensine showed an RR of 0.55 (95%CI 0.28–1.06; NNT = 3). SSRIs (sertraline or citalopram) reduced Beck Depression Inventory (BDI) scores by 4.90 points compared with cognitive behavioral therapy.Conclusion: SSRIs are effective to reduce depressive symptoms in PWE, with venlafaxine representing a viable alternative for non-responders. However, clinicians should carefully consider potential drug-drug interactions, particularly CYP450 enzyme inhibition, which may increase antiepileptic drug levels and require dose adjustments and close monitoring.